RIALTO: Rekonstrukcija dvoetažnega Meljskega mostu na Dravi - Černigoj, Andrej; Ebenšpanger, Tomaž; Šprah, Nataša (2017)
RIALTO: Reconstruction of the Two-storey Meljski Most on Drava River. If they are in Venice, then there must be Rialto. The seemingly simple reason for this year's selection of the topic of a seminar paper is in fact much more profound. In Studio III, for several years now, we are studying the possibility that urbanization in the area of ​​the city center will be closer to the Drava River, which, after the flooding of the Zlatoličje HPP in 1969, turned into an attractive lake. The arrangement of the periphery of the lake with a circular path and a lively urban program, which in this part, as in Lent, should be subordinated to the green landscape arrangement along the two banks of the Drava, could eventually create a unique central city ambience. From this wider context, the idea of ​​urbanization of the two-storey Meljski most (V. Ačanski, Gradis, 1985) is also derived. In this way, in Studio III, in addition to the basic pedagogical goals, we are pursuing the current developments in the field of managing cities in the home and abroad, and with the more unrestrained way of thinking, we explore alternative new ideas for implementation in Maribor.
Keywords: two-storeyed Melje bridge urbanization; urbanization along the Drava river; architecture; teaching process; exhibition of student projects